2016
DOI: 10.1007/s11269-016-1369-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surrogate Measures for the Reliability and Redundancy of Water Distribution Systems

Abstract: An investigation into the effectiveness of surrogate measures for the hydraulic reliability and/or redundancy of water distribution systems is presented. The measures considered are statistical flow entropy, resilience index, network resilience and surplus power factor. Looped network designs that are maximally noncommittal to the surrogate reliability measures were considered. In other words, the networks were designed by multi-objective evolutionary optimization free of any influence from the surrogate measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 62 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…The relationship between flow entropy and resilience (Dunn and Wilkinson 2017) as characterised by reliability and failure tolerance (Praks et al 2015) was shown previously to be strong (Czajkowska and Tanyimboh 2013;Saleh and Tanyimboh 2016;Tanyimboh et al 2016). Other reliability and redundancy surrogates in the literature include various resilience indices (Jayaram and Srinivasan 2008;Liu et al 2016;Prasad and Park 2004;Todini 2000).…”
Section: Network Flow Entropymentioning
confidence: 91%
See 1 more Smart Citation
“…The relationship between flow entropy and resilience (Dunn and Wilkinson 2017) as characterised by reliability and failure tolerance (Praks et al 2015) was shown previously to be strong (Czajkowska and Tanyimboh 2013;Saleh and Tanyimboh 2016;Tanyimboh et al 2016). Other reliability and redundancy surrogates in the literature include various resilience indices (Jayaram and Srinivasan 2008;Liu et al 2016;Prasad and Park 2004;Todini 2000).…”
Section: Network Flow Entropymentioning
confidence: 91%
“…Other reliability and redundancy surrogates in the literature include various resilience indices (Jayaram and Srinivasan 2008;Liu et al 2016;Prasad and Park 2004;Todini 2000). Recent comparative assessments of the surrogates include Atkinson et al (2014), Gheisi and Naser (2015), Liu et al (2014Liu et al ( , 2016 and Tanyimboh et al (2016). Gheisi and Naser (2015) and Tanyimboh et al (2016) observed that flow entropy had a significantly stronger positive correlation with reliability and failure tolerance than the available alternatives.…”
Section: Network Flow Entropymentioning
confidence: 99%
“…With the expansion of the application field of information entropy, Awumah et al [19] first applied information entropy to the reliability analysis of the water supply pipe network system. Nodal flow entropy and system flow entropy indexes are proposed to measure the uncertainty of path selection and pipe network redundancy [20].…”
Section: The Basic Theory Of Surplus Power Entropymentioning
confidence: 99%
“…Other researchers (Alvisi and Franchini [119], Di Nardo and Natale [120] and Campbell et al [121]) combined surrogate measures with graph theory for water-loss detection and pressure management in district metered areas (DMAs). Meanwhile, Raad et al [66], Baños et al [71], Greco et al [122], and Tanyimboh et al [123] compared the performances of surrogate measures, mixed reliability index, flow entropy, network entropy, and the surplus energy factor.…”
Section: Research Progressesmentioning
confidence: 99%